Alteplase for acute ischemic stroke in patients aged >80 years: pooled analyses of individual patient data - Bluhmki, Erich; Danays, Thierry; Biegert, Gabriele; Hacke, Werner; Lees, Kennedy R. (Stroke, 2020)
BACKGROUND/PURPOSE: Expert guidelines specify no upper age limit for alteplase for thrombolysis of acute ischemic stroke (AIS) but, until recently, European regulatory criteria restricted its use to patients aged 18 to 80 years. We performed pooled analyses of randomized controlled trial (RCT) and registry data to evaluate the benefit-risk profile of alteplase for AIS among patients aged >80 years to support a regulatory application to lift the upper age restriction. METHODS: Individual patient data were evaluated from 7 randomized trials of alteplase (0.9 mg/kg) versus placebo or open control for AIS, and the European SITS-UTMOST registry database. Clinical outcomes, including good functional outcome (score 0-1, modified Rankin Scale day 90 or Oxford Handicap Score day 180), were evaluated in the full RCT and registry populations, and specified age-based subgroups (≤80 or >80 years) who met existing European regulatory criteria for alteplase, excluding upper age restriction. RESULTS: Regardless of treatment allocation, 90-day mortality was lower among RCT patients aged ≤80 versus >80 years who otherwise met existing European regulatory criteria (246/2405 [10.2%] versus 307/1028 [29.9%], respectively). Among patients aged >80 years, alteplase versus placebo was associated with a higher proportion of good stroke outcome (modified Rankin Scale score 0-1; 99/518 [19.1%] versus 67/510 [13.1%]; P=0.0109) and similar 90-day mortality (153/518 [29.5%] versus 154/510 [30.2%]; P=0.8382). The odds of a good stroke outcome following alteplase allocation in the full RCT population were independent of age (P=0.7383). Good stroke outcome was reported for almost half (4821/11 169 [43.2%]) of the patients who received alteplase in routine practice. Outcomes in routine practice supported those achieved in RCTs. CONCLUSIONS: Alteplase for AIS has a positive benefit-risk profile among patients aged >80 years when administered according to other regulatory criteria. Alteplase for AIS should be evaluated on an individual benefit-risk basis.
Gesehen am 16.09.2020